Effects of varying types and amounts of herbivory and nutrient enrichment on a tropicalizing seagrass meadow - Rodriguez, Alexandra R.; Marco-Méndez, Candela; Campbell, Justin; Heck, Kenneth L. (Frontiers in Marine Science, 2022)
Climate change is impacting marine ecosystem community dynamics on a global scale. While many have assessed direct effects of climate change, indirect effects on marine ecosystems produced by biotic interactions remain poorly understood. For example, warming-induced range expansions and increased consumption rates of herbivores can lead to significant and unexpected changes in seagrass-dominated ecosystems. To better understand the threats tropicalization presents for the functioning of turtlegrass (Thalassia testudinum) meadows, we focused on the extensive turtlegrass beds of St. Joseph Bay, Florida in the northern Gulf of Mexico, a location with increasing numbers of tropically-associated green turtles. Our goals were to investigate experimentally how different grazing rates (natural and simulated),including high levels reflective of green turtle herbivory, coupled with nutrient supply, might alter turtlegrass structure and functioning in a higher latitude, subtropical turtlegrass meadow. We found that 4 months of varying levels of herbivory did not affect turtlegrass productivity, while 7 months of herbivory reduced percent cover, and 10 months reduced shoot density. Nutrient additions had few important effects. Ten months into the study, a massive recruitment of the herbivorous sea urchin (Lytechinus variegatus), whose densities reached 19 urchins/m2 completely overgrazed our study area and a large portion of the lush turtlegrass meadows of St. Joseph Bay. While local turtlegrass overgrazing had been previously noted at these urchin densities, a total loss of seagrass in such a large area has rarely ever been recorded. Overgrazing of the kind we observed, likely a result of both urchin and increasing green turtle grazing, can result in the loss of many key ecosystem services. As tropicalization continues, understanding how changes in biotic interactions, such as increased herbivory, affect higher latitude seagrass meadows will be necessary for their proper management and conservation.